2015
DOI: 10.1021/jacs.5b05507
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Addressable Cavities within Metal–Organic Cage-Cross-Linked Polymeric Hydrogels

Abstract: Here we report a new class of hydrogels formed by polymers that are cross-linked through subcomponent selfassembled metal−organic cages. Selective encapsulation of guest molecules within the cages creates two distinct internal phases within the hydrogel, which allows for contrasting release profiles of related molecules depending on their aptitude for encapsulation within the cages. The hydrogels were fabricated into microparticles via a droplet-based microfluidic approach and proved responsive to a variety of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
123
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(127 citation statements)
references
References 70 publications
1
123
0
2
Order By: Relevance
“…Work by Foster et al further demonstrated that hydrogels comprising a metal-organic cage can selectively bind benzene in the presence of the similarly sized anisole, and release this guest upon the addition of furan, a competitive binding agent. 344 It is noted that since non-encapsulated guests may leave the extrinsic pores of a gel by ambient diffusion, gels with intrinsic porosity enable the controlled delivery of multiple reagents at differing rates, with potential applications in catalysis, drug delivery and chemical purification. 56 In spite of their stability, DTEs frequently boast a high rate of isomerisation when illuminated, even in the solid state.…”
Section: Articlementioning
confidence: 99%
“…Work by Foster et al further demonstrated that hydrogels comprising a metal-organic cage can selectively bind benzene in the presence of the similarly sized anisole, and release this guest upon the addition of furan, a competitive binding agent. 344 It is noted that since non-encapsulated guests may leave the extrinsic pores of a gel by ambient diffusion, gels with intrinsic porosity enable the controlled delivery of multiple reagents at differing rates, with potential applications in catalysis, drug delivery and chemical purification. 56 In spite of their stability, DTEs frequently boast a high rate of isomerisation when illuminated, even in the solid state.…”
Section: Articlementioning
confidence: 99%
“…Aida et al have shown that CAHB interaction between anionic clay nanosheets and dendritic molecular binders containing multiple guanidinium ions facilitated the cross-linking of the clay nanosheets and formed hydrogels 39 . Recently, Johnson et al and Nitschke et al reported the self-assembly of soluble polymers having coordinating end groups with metal ions, leading to the formation polymeric gel that consisted of in-situ formed metal-organic cage at the junction of cross-linked polymers 4042 .…”
Section: Introductionmentioning
confidence: 99%
“…In synthetic polymeric system self-healing can be of two types; (i) induced self-healing like pH 34 , light 35 , heat 36 etc. and (ii) non-induced self-healing via formation of ionic interaction 34 , H-bonding 37 , π-π stacking 38 , metal coordination 39 etc. Until now reports based on hydrogels having multifunctional ability like self-healing and fluorescent properties are rare.…”
Section: Introductionmentioning
confidence: 99%